Differentiation propensity, safety, and therapeutic potential of mesenchymal stem cells of dental origin / Sabri Musa - Sabri , Musa (2020)
Introduction: A new area in medical research has emerged with the discovery of mesenchymal stem cells (MSCs) and their ability to differentiate into other cell types. Specifically, these cells are found in various tissues and have been utilized in the field of regenerative medicine to support tissue repair as well as in cell replacement. Lately, MSCs of dental origin have been the main players used for regenerative purposes although subtle differences based on their tissue source separate them. Objectives: This study aims to determine the differential propensity, safety, and potential therapeutic applications of dental-derived MSCs. This involves examining various aspects of the cells ranging from their basic characteristics, dynamics of miRNA, differential potential, and immunomodulatory effects. Methods: The first investigation compared the basic characteristics of deciduous and permanent teeth in terms of their proliferation rates, gene expressions profile, and lineage-specific proclivity over 5 passages. The second study looks into the differentiation ability of dental stem cells in particular, into hepatic lineage cells so as to examine the efficacy of human platelet lysates by substituting fetal bovine serum. The third research work deals with immunologic properties of dental stem cells originated from deciduous and permanent teeth, and periodontal ligament cells. All these cells were subjected into a long-term culture condition. The proteins were validated using Luminex platform. The fourth research work compared the immunomodulatory properties of dental pulp from healthy and inflamed teeth. Their immunosuppressive effects were compared on phytohemagglutinin-induced T cell proliferation. The fifth research work profiled the miRNA regulations in dental pulp stem cells in comparison to bone marrow stem cells by subjecting them to ingenuity analysis. Finally, the sixth and seventh works reviewed the use of dental pulp stem cells for cardiac regeneration and wound healing in skin, respectively. Results: The dental pulp stem cells from deciduous teeth showed higher proliferation rates over the 5 passages while retaining their plasticity compared to those from permanent teeth which tended towards neuronal lineage. As for substitution of human platelet lysates, the efficacy of dental pulp stem cells compared to fetal bovine serum was reflected in higher proliferation rates and the ability to differentiate into hepatic lineage. The work on immunomodulatory genes established that the dental pulp stem cells of deciduous teeth surpassed other cells in terms of expressing immune genes at a late passage despite being cultured under identical conditions. In comparison to their healthy counterparts, inflamed dental pulp stem cells showed minimal pro-inflammatory tendencies and in stimulating anti-inflammatory responses. In addition, miRNA expression in dental pulp stem cells showed integration as a group rather than having a solitary role in the basic regulation of the stem cells. Finally, the two review papers noted the capability of dental stem cells for cardiac regeneration via the PI3-Kinase/Akt signaling pathway while providing greater understanding of the growth factors and cytokines in stem cells for the management of skin wound healing. Conclusions: The results strongly suggest that stem cells of dental origin may be good candidates for regenerative therapy purposes. However, further work is required mainly on in vitro and in vivo aspects to determine their safety and efficacy for use in regenerative medicine.